The Implementation of Classical Guidance using the 'Find Me' Game to Enhance High School Students' Self-defense Skills Against Bullying through Problem-Based Learning - Agustin, Prisca Aulia; Setyaputri, Nora Yuniar (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to examine the effectiveness of implementing Problem-Based Learning (PBL) through the "Find Me" game media in enhancing self-defense behavior against bullying among 10th-grade students (Class X-6) at SMAN 2 Kediri. The research employed a guidance and counseling action research method with 40 student participants. The intervention was conducted in two cycles using a pretest-posttest design. Data were analyzed using the flow model. The results showed a significant improvement in self-defense behavior against bullying, increasing from 12.5% at the initial stage to 77.5% after the intervention. These findings indicate that applying PBL combined with the "Find Me" game media effectively develops students' ability to defend themselves in bullying situations. This research offers practical implications for school counselors and educators in designing innovative, student-centered interventions using cognitive and behavioral approaches to address bullying in the school environment.